Making it personal: science communication for the masses. Issue 8 (August 2021) - Sullivan, William J.; Strathdee, Steffanie A.; Hotez, Peter J.
Abstract : To curtail the rising tide of antiscience threatening the health and progress of society, scientists are increasingly engaging with the public. Here, we describe our approach to write accessible books based on personal stories as a means to help spread scientific literacy to those who normally do not read science.